URGENSI PENGUNAAN LANDASAN FILOSOFIS, SOSIOLOGIS, DAN YURIDIS DALAM KEPUTUSAN KEPALA DAERAH - Ira, Lisa (Jurnal Res Justitia: Jurnal Ilmu Hukum, 2024)
Regional autonomy gives the rights, authorities, and obligations to the regions to regulate and manage their own government affairs and the interests of the local community, one of which is to make regional policies such as Regional Regulations, Regional Head Regulations, Regional Head Decisions and others. Regional head decisions are one type of regional legal product which is one of the authorities of the regional head. Philosophical, sociological, and juridical foundations are part of the elements of good legislation. this study discusses the urgency of using philosophical, juridical, sociological foundations in the Decree of the Regional Head because the Decree is a determination that is not part of the regulation unless it fulfils the requirements as referred to in Law 12 of 2011 concerning the Formation of Legislation. The research method used in this research is the normative juridical method or it can be interpreted that this research is conducted with literature or secondary data. With a statutory approach and analytical approach. The results show that in the context of drafting regulations and decisions at the regional level, including decisions of regional heads, containing philosophical, sociological, and juridical foundations is not always explicitly required for every regent's decision. However, these principles are highly recommended and often applied in practice to ensure the quality and legitimacy of such decisions